2008
DOI: 10.1111/j.1365-2222.2008.03004.x
|View full text |Cite
|
Sign up to set email alerts
|

MALDI‐TOF MS analysis of labile Lolium perenne major allergens in mixes

Abstract: Lol p 1 and Lol p 5 degradation is responsible for the loss of the biological activity of L. perenne pollen extract when co-incubated with protease-rich fungal and cockroach extracts in the same vial for months in the absence of glycerol as a preserving agent. The integrity of these major allergens must be preserved to increase the vaccine stability and to assure efficacy when mixes are used for immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…First investigations of plant‐related samples demonstrated the analytical potential of the approach for the qualitative and quantitative analysis of plant carotenoids . Recently, it was shown that MALDI‐TOFMS can be used for the investigation of purified allergenic molecules in pollen, and, furthermore, also to obtain whole pollen fingerprint spectra for pollen classification . This application is of crucial interest, since pollen identification is still a challenging analytical task that is based mainly on genus‐specific pollen morphology.…”
mentioning
confidence: 99%
“…First investigations of plant‐related samples demonstrated the analytical potential of the approach for the qualitative and quantitative analysis of plant carotenoids . Recently, it was shown that MALDI‐TOFMS can be used for the investigation of purified allergenic molecules in pollen, and, furthermore, also to obtain whole pollen fingerprint spectra for pollen classification . This application is of crucial interest, since pollen identification is still a challenging analytical task that is based mainly on genus‐specific pollen morphology.…”
mentioning
confidence: 99%
“…Enzymatic activities in allergenic extracts, particularly proteases, are known to negatively affect the quality and activity of allergenic products. [47][48][49][50][51] JJAV possesses various enzymatic activities 2 ; however, no studies had described the presence of proteases in this venom to date. We detected one type of protease (leucine aminopeptidase) in JJAV with moderate levels of activity, and it is possible that this endogenous protease degrades high MW proteins in JJAV AI.…”
Section: Discussionmentioning
confidence: 99%
“…Since the nature and chemical composition of specific allergens are still widely unknown, electrophoretic and immunologic techniques to identify specific pollen allergens have been applied in combination with matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOFMS). With these techniques the structures of lipids, proteins, glycans, and saccharides released from the sporopollenin cage could be identified over a molecular mass range from 4000 to 18000 Da . Many of these results were obtained after harsh sample treatment causing damage of the sporopollenin cage, accompanied by a possible modification of chemical components.…”
Section: Methodsmentioning
confidence: 99%
“…With these techniques the structures of lipids, proteins, glycans, and saccharides released from the sporopollenin cage could be identified over a molecular mass range from 4000 to 18000 Da. [11][12][13][14][15][16][17][18][19] Many of these results were obtained after harsh sample treatment causing damage of the sporopollenin cage, accompanied by a possible modification of chemical components. A new, gentler sample preparation method followed by MALDI-TOF mass spectral analysis was recently presented by our group.…”
Section: Rationalementioning
confidence: 99%